2019
DOI: 10.1016/j.cemconres.2019.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Frost resistance of concrete with high contents of fly ash - A study on how hollow fly ash particles distort the air void analysis

Abstract: Cenospheres are hollow fly ash particles. When performing air void analysis on a contrast enhanced plane section, air inclusions in cenospheres are counted as air voids. In the present study, air void analyses for air entrained concrete mixtures with fly ash (up to 50% of binder mass) were corrected based on chord counting for non-air entrained paste samples with various contents of fly ash. The correction only lead to a small reduction of the total air content, but it increased the spacing factor up to 25%. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…7 shows that the air void parameters are refined after the addition of fly ash, fiber, MgO and SRA, whereas the refinement effects of fly ash and PVA fiber are more significant compares with those of MgO and SRA. A similar observation has been revealed by Hasholt et al 24 , who reported that the addition of fly ash deceased effectively the spacing factor due to two mechanisms, the first mechanism was the addition of fly ash resulted in an increase in paste volume because of its lower density, the other one was the pore refinement effect of fly ash that transformed the larger pores into smaller pores. Şahmaran et al 20 reported that much finer air voids could be entrained in concrete due to the inclusion of PVA fiber, because the addition of PVA fiber generally increases the viscosity of the fresh concrete mixture and consequently prevents many entrapped air voids in concrete merging into large ones.…”
Section: Characteristics Of Thesupporting
confidence: 82%
See 2 more Smart Citations
“…7 shows that the air void parameters are refined after the addition of fly ash, fiber, MgO and SRA, whereas the refinement effects of fly ash and PVA fiber are more significant compares with those of MgO and SRA. A similar observation has been revealed by Hasholt et al 24 , who reported that the addition of fly ash deceased effectively the spacing factor due to two mechanisms, the first mechanism was the addition of fly ash resulted in an increase in paste volume because of its lower density, the other one was the pore refinement effect of fly ash that transformed the larger pores into smaller pores. Şahmaran et al 20 reported that much finer air voids could be entrained in concrete due to the inclusion of PVA fiber, because the addition of PVA fiber generally increases the viscosity of the fresh concrete mixture and consequently prevents many entrapped air voids in concrete merging into large ones.…”
Section: Characteristics Of Thesupporting
confidence: 82%
“…μm, 219 μm, 235 μm and 231 μm, respectively, all of which are lower than the generally accepted value of 250 mm for a good freeze-thaw durability 20,22,24 . It is widely accepted that the smaller the spacing factor, the better the frost resistance, and vice versa 22,24 .…”
Section: Characteristics Of Thementioning
confidence: 63%
See 1 more Smart Citation
“…With the development of science and technology and the protection of the ecological environment, the frost resistance of concrete can be significantly improved by adding waste rubber into concrete [ 2 , 3 ]. At the same time, due to the small particle size and large specific surface area of nano-SiO 2 , adding the same amount of nano-SiO 2 instead of cement into concrete can give play to its fine particle filling, good pozzolanic and nucleation effects, improving the interface transition zone structure, compactness, and strength, especially the early strength and frost resistance [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The white substance used to highlight the air voids will be present in all indents and grooves of the plane section surface -not only air voids but also e.g. pull-outs accidentally made during specimen preparation, porosities in aggregates [12,13], and hollow fly ash particles [13,14]. The operator will know the difference, but the computer will interpret all white areas of the plane section as air voids.…”
Section: Introductionmentioning
confidence: 99%